NON-STANDARD FORMS OF EMPLOYMENT IN BUSINESS ORGANIZATIONS - A. E. Chekanov (Модернизация, инновация, развитие, 2015)
The article discusses the emergence and development of non-standard forms of employment and flexible working. The causes of their use reflects the results of research conducted in the workplace. Non-standard forms of employment and attractive today as they allow to expand the circle of the workforce.